2021
DOI: 10.1186/s13045-021-01035-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibody–drug conjugates in solid tumors: a look into novel targets

Abstract: Antibody–drug conjugates (ADCs) are a relatively new class of anticancer agents designed to merge the selectivity of monoclonal antibodies with cell killing properties of chemotherapy. They are commonly described as the “Trojan Horses” of therapeutic armamentarium, because of their capability of directly conveying cytotoxic drug (payloads) into the tumor space, thus transforming chemotherapy into a targeted agent. Three novel ADCs have been recently approved, i.e., trastuzumab deruxtecan, sacituzumab govitecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 127 publications
(148 reference statements)
1
138
0
Order By: Relevance
“…Sacituzumab govitecan is an ADC consisting of a fully humanized IgG1 anti-Trop2 antibody and the active metabolite of irinotecan (SN-38), a topoisomerase I inhibitor. The antibody is linked to SN-38 by a hydrolysable linker, which causes the release of drug molecules into the tumor microenvironment, thereby killing adjacent tumor cells (bystander effect) [ 45 , 46 ]. Sacituzumab govitecan was first approved by the US Food and Drug Administration for the treatment of triple-negative breast cancer and later authorized for treating lung cancer and urothelial carcinoma [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sacituzumab govitecan is an ADC consisting of a fully humanized IgG1 anti-Trop2 antibody and the active metabolite of irinotecan (SN-38), a topoisomerase I inhibitor. The antibody is linked to SN-38 by a hydrolysable linker, which causes the release of drug molecules into the tumor microenvironment, thereby killing adjacent tumor cells (bystander effect) [ 45 , 46 ]. Sacituzumab govitecan was first approved by the US Food and Drug Administration for the treatment of triple-negative breast cancer and later authorized for treating lung cancer and urothelial carcinoma [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antibody is linked to SN-38 by a hydrolysable linker, which causes the release of drug molecules into the tumor microenvironment, thereby killing adjacent tumor cells (bystander effect) [ 45 , 46 ]. Sacituzumab govitecan was first approved by the US Food and Drug Administration for the treatment of triple-negative breast cancer and later authorized for treating lung cancer and urothelial carcinoma [ 45 ]. Bardia et al recently reported the results of a phase III trial for relapsed or refractory metastatic triple-negative breast cancer (NCT02574455) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, prior to Kadcyla ® , the treatment of solid tumors with ADCs fell short due to numerous biological barriers in the tumor microenvironment (e.g., poor vascularization, diffusion through dense stroma, overcoming tumor interstitial fluid pressure) which limited drug penetration. Secondly, unlike hematologic malignancies, the concept of lineage-specific antigen expression is not applicable to solid tumors, for which the antigens expressed are mainly “tumor associated” rather than “tumor specific” [ 70 ]. This implies both a share of on-target/off-tumor toxicity and thus reduced intra-tumoral drug delivery.…”
Section: Fda Approved Adcsmentioning
confidence: 99%
“…Antibody-drug conjugates (ADCs) represent a new generation of highly potent antineoplastic drugs (19). These drugs are built by attaching a small molecule of an anticancer drug (payload) or another therapeutic agent to an antibody, using either a permanent or a labile linker.…”
Section: Antibody-drug Conjugates (Adc)mentioning
confidence: 99%